2022
DOI: 10.1021/acs.jpca.2c03053
|View full text |Cite
|
Sign up to set email alerts
|

X3Σg → b1Σg+ Absorption Spectra of Molecular Oxygen in Liquid Organic Solvents at Atmospheric Pressure

Abstract: Spectra and absorption coefficients of the forbidden 765 nm X 3 Σ g − → b 1 Σ g + transition of molecular oxygen dissolved in organic solvents at atmospheric pressure were recorded over a 5 m path length using a liquid waveguide capillary cell. The results show that it is possible to investigate this weak near-infrared absorption transition in a common liquid hydrocarbon solvent without the need for a potentially dangerous high oxygen pressure. Proof-ofprinciple data from benzene, toluene, chlorobenzene, bromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…The latter aligns with the quenching mechanisms elucidated for the [Cr III (bipy) 3 ] 3+ complex operating through an energy-transfer process from the Cr( 2 E) excited state to the ground-state triplet 3 O 2 . This finding may apply to other Cr(III) complexes, as depicted in Figure S45 (and Table S10), showing an increasing dioxygen insensitivity as their emission maxima deviate from the absorption maximum of dioxygen (setting at 760 nm). Finally, one should not lose sight that the dioxygen sensitivity in the general case of Cr(III) complexes depends on multiple parameters whose main contribution(s) may be difficult to elucidate or to define absolute trends because they appear to be complex-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…The latter aligns with the quenching mechanisms elucidated for the [Cr III (bipy) 3 ] 3+ complex operating through an energy-transfer process from the Cr( 2 E) excited state to the ground-state triplet 3 O 2 . This finding may apply to other Cr(III) complexes, as depicted in Figure S45 (and Table S10), showing an increasing dioxygen insensitivity as their emission maxima deviate from the absorption maximum of dioxygen (setting at 760 nm). Finally, one should not lose sight that the dioxygen sensitivity in the general case of Cr(III) complexes depends on multiple parameters whose main contribution(s) may be difficult to elucidate or to define absolute trends because they appear to be complex-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that absorbance measurements can be performed at ambient pressures using a waveguide capillary cell that has a path length of 5 m and does not require a large volume of the solvent. 770 However, due to limitations in the transmission spectrum of the waveguide, we were only able to obtain data for the 765…”
Section: Molar Absorption Coefficients Absorption Coefficients For Th...mentioning
confidence: 99%
“…9,13 Although eq 35 was derived for an allowed transition, 774 the evidence obtained thus far indicates that it is nevertheless also applicable to the weak forbidden transitions of dissolved oxygen. 69,132,768,770 In this way, transition probabilities that may be easier to quantify in emission can still be correlated to molar absorption coefficients, with the caveat that assumptions may have to be made regarding the dependence of ε lower→upper on ν (i.e., the integral in eq 35). For oxygen, however, errors that derive from the latter may be small due to the narrow spectral bandwidths of the transitions.…”
Section: Molar Absorption Coefficients Absorption Coefficients For Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic energy transfer (ET) from excited triplet photosensitizers to molecular oxygen is the most common way to produce singlet oxygen using light. Direct photoexcitation of oxygen is limited due to spin conservation restrictions and a very small molar absorption coefficient (ε 765nm in benzene = (1.4 ± 0.1) × 10 –3 L mol –1 cm –1 ) (Figure d). , Singlet oxygen is relatively long-lived in liquid water (lifetime, τ Δ , ∼3.5 μs) and its diffusion coefficient ( D = 2 × 10 –5 cm 2 s –1 ) corresponds to an average diffusion length [= (2 Dτ Δ ) 1/2 ] of approximately 170 nm within two lifetimes in water . Because the rheological properties of the cytoplasm differ from those of water, great effort has been made to measure the lifetime of 1 O 2 in living cells through time-resolved phosphorescence measurements.…”
Section: Photosensitization Takes Photodamage Deepermentioning
confidence: 99%